PENGARUH KEPEMIMPINAN, BEBAN KERJA, DAN LINGKUNGAN KERJA TERHADAP KOMITMEN ORGANISASI PETUGAS JAGA DI LEMBAGA PEMASYARAKATAN KLAS II A MATARAM - Riva dilyanti; lalu suparman; hermanto hermanto (Master of Management, Mataram University, 2017)
This research is aimed at (1) determining the significant effect of leadership on theorganization commitment, (2) determining the significant effect of work load on the organizationcommitment, (3) determining the significant effect of work environment on the organizationlcommitment.The data were collected through census method. The population the research are all 57employees working as guard in Correctional Institutions of Class II A Mataram. All of them are therespondents of this research. The analysis is using multiple regression analysis with SPSS version17.0.The research showed that the organization commitment of the guards is very high. This resultis supported by the leadership of the head of Correctional Institutions during the well running of hisfunctions, the work load of the guards is quite hard, and the work environment as the guards felt isvery good. The statistic analysis showed that : (1) the leadership has positive and significant effect onthe organization commitment. This means that the better the head of correctional institutions runshis function, the better the organization commitment of the guards and vice-versa, (2) the work loadof the guards has negative and significant effect on the organization commitment. This means thatthe more work load of the guards, the worse the organization commitment of the guards and viceversa,(3) the work environment has positive and significant effect on the organization commitment.This means that the better the work environment for the guards, the better the organizationcommitment on the guards and vice-versaKeywords : Leadership, Work Load, Work Environment, and Organization Commitment